Menimbang Sitor Situmorang - Teeuw, A. (Jakarta : Komunitas Bambu : KITLV, 2009)
Literary criticism on Sitor Situmorang's works; festschrift in honor of Sitor Situmorang, an Indonesian writer.
Keywords: Situmorang, Sitor, -- 1923- -- Criticism and interpretation; Situmorang, Sitor, -- 1923-.; Authors, Indonesian -- 20th century